Intelligence sleep monitoring system - Nor Azlina Binti Semiran@Saring (School of Microelectronics, University Malaysia Perlis, 2015)
This project is about the movement detection using accelerometer and show the movement data in mobile application. The accelerometer used in this project is ADXL335. This project aim to build a sensor detection system which is transmit and receive the data wirelessly to another device. This system used during sleep where put the device on hand. When the movement detect, the accelerometer capture the trigger and count the movement. The data collected store in the embedded system of Arduino Uno before transmit to the mobile application. The data transmit wirelessly via the Bluetooth connection. Wireless is no need the wire cable to set up. This is one of the advantage that using wireless. In the application, it will make call function to get the data from the embedded system. From the result, people that have low number of movement during sleep have good quality in sleep. While, people that have large number of movement during sleep have bad sleep quality.